(untitled) (Journal of Pharmaceutical Negative Results, 2022)
Coronavirus disease 2019 (COVID-19) is a kind of viral pneumonia which is caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2). The emergence of SARS-CoV-2 has been marked as the third introduction of a highly pathogenic coronavirus into the human population after the severe acute respiratory syndrome coronavirus (SARS-CoV) and the Middle East respiratory syndrome coronavirus (MERS-CoV) in the twenty-first century, Forcing scientists to continue Research to discover a vaccine for this disease in in request to control and boundary the range Of the disease. This study was designed to hit upon out whether here are side effects on vaccinated people who received covid-19 vaccine or not by measuring the body's vitality by some of biochemical tests.Subjects:75 individuals between women and men aged (17-68 years)were enrolled in this study .Several biochemical tests were performed on them before taking the vaccine ,a week to10 days after the first dose, and a week to 10 days after the second dose of covid-19 vaccine. RESULTS: All subjects in this Study received the Pfizer-Bio N Tech vaccine and no systemic side effects were Observed in subjects vaccinated during the study period. Conclusions: From the Results of the current study, there were no abnormal biochemical markers, increased, or changes in basic body functions after receiving the Pfizer vaccine.